2021
DOI: 10.3390/pathogens10050581
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Minnesota Biofilms, Susceptibility to Biocides, and Molecular Characterization

Abstract: The presence of virulence genes, phylogenetic relationships, biofilm formation index (BFI), and ultrastructure in S. Minnesota at different temperatures (4, 25, and 36 °C) were analyzed. In addition, the ability of biocidal agents (chlorhexidine1%, sodium hypochlorite 1%, and peracetic acid 0.8%) to inhibit biofilms formed by 20 strains isolated from broiler slaughter plants from two Brazilian companies in 2009, 2010, and 2014 was determined. The presence of specific genes was evaluated by PCR and phylogeny be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…The same point-mutations here detected in gyrA (p.S83F), parC (p.T57S), and qnrB19, have been reported in Brazilian poultry (de Melo et al, 2021;Monte et al, 2019) and all our isolates but one (which only harboured parC) showed complete or low-level resistance to ciprofloxacine and resistance to nalidixic acid according to the breakpoints (European Committee on Antimicrobial Susceptibility Testing…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The same point-mutations here detected in gyrA (p.S83F), parC (p.T57S), and qnrB19, have been reported in Brazilian poultry (de Melo et al, 2021;Monte et al, 2019) and all our isolates but one (which only harboured parC) showed complete or low-level resistance to ciprofloxacine and resistance to nalidixic acid according to the breakpoints (European Committee on Antimicrobial Susceptibility Testing…”
Section: Discussionsupporting
confidence: 86%
“…Genes involved in biofilm formation and acid tolerance were found in all of our isolates (Table 1 ). de Melo et al ( 2021 ) analysed the in vitro biofilm formation in SM from Brazilian poultry detecting genes for adhesion ( agfA/csg ), biofilm formation ( lpfA ), and survival under oxidative stress ( sodC ). These were also present in our isolates, except for sodC in SM, exemplifying the variety of circulating strains, even if sampled in the same geographical regions (Southeast Brazil).…”
Section: Discussionmentioning
confidence: 99%
“…CJ contains a complex mixture of carbohydrates (0.06%) and protein (2.79%), giving an ideal medium for the proliferation and survival of bacteria and allows the formation of microlayers on the surfaces that aid in bacterial fixation. The influence of the increase promoted by the CJ was also identified in the Campylobacter jejuni, S. Typhimurium, S. Enteritidis, and S. Minnesota (Cappitelli et al, 2014;Li et al, 2017;Melo et al, 2017;de Melo et al, 2021). Despite the increase of extracellular matrix, CJ did not increase the number of viable cells, which is a strain-dependent characteristic.…”
Section: Phenotype Of Biofilms By Shmentioning
confidence: 85%
“…The sessile structures of SH showed an effective increase in their intensity, according to the BFI, at higher temperatures (25 and 37 • C). According to de Melo et al (2021), the use of higher temperatures also favors the production of biofilms in S. Minnesota. The influence of temperature on the establishment of biofilms is described as a serovar-and strain-dependent characteristic.…”
Section: Phenotype Of Biofilms By Shmentioning
confidence: 99%